Loyalitas Pengguna Sepatu Ventela: Kualitas Produk Dan Harga Melalui Kepuasan Konsumen - Subhan, Subhan; Hidayati, Nur; Farida, Eka (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The competition in the local shoe industry is getting tighter, along with the increasing public interest in quality local products. Ventela shoes are a local brand that is quite popular in Indonesia and have the challenge of maintaining customer loyalty. Consumer loyalty is determined by consumer satisfaction, product quality, and price. The purpose of this study is to analyze the effect of product quality and price on loyalty through consumer satisfaction. The type of research used is explanatory. The population of the study is not known with certainty with the purposive sampling technique, so the number of samples is 65 respondents. Data collection through questionnaires and analyzed using the SEM-PLS method. The results of the study show that product quality and price have a significant effect on consumer satisfaction. Product quality and price do not have a significant effect, while consumer satisfaction has a significant effect on loyalty. Product quality has a significant effect on loyalty through consumer satisfaction, while price has no significant effect.